2018
DOI: 10.1080/0092623x.2018.1462277
|View full text |Cite
|
Sign up to set email alerts
|

Consensual Nonmonogamy in Pregnancy and Parenthood: Experiences of Bisexual and Plurisexual Women With Different-Gender Partners

Abstract: The current study constitutes a qualitative investigation of experiences with and perceptions of consensual nonmonogamy (CNM) among a sample of 21 bisexual and plurisexual women with different-gender partners. Participants from Massachusetts, USA, and Toronto, Canada, were interviewed four times during pregnancy and the postpartum period. Using an inductive qualitative approach, we found participants were selective about CNM disclosure, and generally apprehensive about stigma surrounding CNM involvement. Addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…While being a parent may be more privileged in some social contexts, in this study, being a parent was associated with higher enacted CNM-related stigma. This finding supports previous research that found that sexual minority parents experienced prejudice and judgment from others as a result of their involvement in consensual nonmonogamy (Manley et al, 2018). This finding may be explained by the historical association between parenthood and more traditional (i.e., heteronormative, mononormative) paradigms that view consensual nonmonogamy as a deviation from the norm.…”
Section: Discussionsupporting
confidence: 91%
“…While being a parent may be more privileged in some social contexts, in this study, being a parent was associated with higher enacted CNM-related stigma. This finding supports previous research that found that sexual minority parents experienced prejudice and judgment from others as a result of their involvement in consensual nonmonogamy (Manley et al, 2018). This finding may be explained by the historical association between parenthood and more traditional (i.e., heteronormative, mononormative) paradigms that view consensual nonmonogamy as a deviation from the norm.…”
Section: Discussionsupporting
confidence: 91%
“…These results highlight the importance of finding a chosen social network that provides support and validation, in ways that may not reflect traditional norms of biological or legal familial relationships. Other research has identified similar aspects of community as being important benefits to CNM relationships (Manley et al, 2018;Moors et al, 2017a;Sheff, 2010). In a longitudinal study consisting of interviews and observations of polyamorous families, shared parenting and resources was viewed as a benefit of polyamory (Sheff, 2010).…”
Section: Communitymentioning
confidence: 99%
“…Several parents did highlight communication skills as a strength of polyamorous relationships and communities and as an ability they had intentionally cultivated within their own relationships. The emphasis on communication mirrors previous research in which mothers discussed negotiating changes and setting boundaries to navigate CNM relationships during the transition to parenthood (Manley et al, 2018), as well as other literature on engaged communication as a strength of CNM relationships (Conley and Moors, 2014).…”
Section: Discussionmentioning
confidence: 72%
“…For example, Huebner et al (2012) interviewed gay male parent couples with varied relationship agreements, who reported that becoming parents decreased sexual opportunities with other partners. Similarly, in a study of sexual minority mothers, Manley et al (2018) found that several women who expressed interest in CNM chose to focus on their primary relationship rather than seek new partners or relationship experiences during the pregnancy and postpartum period. Some of the mothers also described how increased caution (e.g., about STI risk, relationship stability, or impacts on family) led them to close the relationship temporarily or necessitated increased communication around boundaries and comfort (Manley et al, 2018).…”
Section: Queer Theory and Cnm Parentingmentioning
confidence: 99%
See 1 more Smart Citation